Cubicles or corner offices? Effects of academic performance on university graduates’ employment likelihood and salary - Soon, Jan Jan; Lee, Angela Siew Hoong *; Lim, Eam Lim; Izian Idris, *; Eng, William Yong Keong * (Taylor & Francis, 2019)
This paper uses a 2016/2017 sample of 1107 freshly minted university graduates from a public and a private university in Malaysia. Against a backdrop of an institutional setting very much different from that of western countries’ and issues of high living costs and graduate unemployment, we analyse how academic performance affects graduates’ employment likelihood, salaries, and salary distribution. Using quantile estimations, we find that academic performance is not a key determinant in whether or not a graduate secures a job upon graduation, and that having better academic performance would only be beneficial if the graduates are working in jobs at the lower half of the salary distribution. We fill the literature gap by analysing how academic performance affects new graduates in terms of where they are on the salary distribution continuum; such analyses are neglected in the literature.